Determining the Effect of Centrifugal Force on the Desired Growth and Properties of PCPDTBT as p-Type Nanowires - Doris, M.; Aziz, F.; Alhummiany, H.; Bawazeer, T.; Alsenany, N.; Mahmoud, A.; Zakaria, R.; Sulaiman, K.; Supangat, A. (SpringerOpen, 2017)
In this study, low-bandgap polymer poly{[4,4-bis(2-ethylhexyl)-cyclopenta-(2,1-b;3,4-b′)dithiophen]-2,6-diyl-alt-(2,1,3-benzothiadiazole)−4,7-diyl} (PCPDTBT) nanostructures have been synthesized via a hard nanoporous alumina template of centrifugal process. Centrifuge has been used to infiltrate the PCPDTBT solution into the nanoporous alumina by varying the rotational speeds. The rotational speed of centrifuge is directly proportional to the infiltration force that penetrates into the nanochannels of the template. By varying the rotational speed of centrifuge, different types of PCPDTBT nanostructures are procured. Infiltration force created during the centrifugal process has been found a dominant factor in tuning the morphological, optical, and structural properties of PCPDTBT nanostructures. The field emission scanning electron microscopy (FESEM) images proved the formation of nanotubes and nanowires. The energy-dispersive X-ray spectroscope (EDX) analysis showed that the nanostructures were composed of PCPDTBT with complete dissolution of the template.